Identification of in vivo Essential Genes of Vibrio vulnificus for Establishment of Wound Infection by Signature-Tagged Mutagenesis - Yamazaki, Kohei; Kashimoto, Takashige; Morita, Mio; Kado, Takehiro; Matsuda, Kaho; Yamasaki, Moeko; Ueno, Shunji (Frontiers in Microbiology, 2019)
Vibrio vulnificus can cause severe necrotic lesions within a short time. Recently, it has been reported that the numbers of wound infection cases in healthy hosts are increasing, for which surgical procedures are essential in many instances to eliminate the pathogen owing to its rapid proliferation. However, the mechanisms by which V. vulnificus can achieve wound infection in healthy hosts have not been elucidated. Here, we advance a systematic understanding of V. vulnificus wound infection through genome-wide identification of the relevant genes. Signature-tagged mutagenesis (STM) has been developed to identify functions required for the establishment of infection including colonization, rapid proliferation, and pathogenicity. Previously, STM had been regarded to be unsuitable for negative selection to detect the virulence genes of V. vulnificus owing to the low colonization and proliferation ability of this pathogen in the intestinal tract and systemic circulation. Alternatively, we successfully identified the virulence genes by applying STM to a murine model of wound infection. We examined a total of 5418 independent transposon insertion mutants by signature-tagged transposon mutagenesis and selected 71 clones as attenuated mutants consequent to disruption of genes by the insertion of a transposon. This is the first report demonstrating that the pathogenicity of V. vulnificus during wound infection is highly dependent on its characteristics: flagellar-based motility, siderophore-mediated iron acquisition system, capsular polysaccharide, lipopolysaccharide, and rapid chromosome partitioning. In particular, these function during the wound infection process and are indispensable for proliferation in healthy hosts. Our results may thus allow the potential development of new strategies and reagents to control the proliferation of V. vulnificus and prevent human infections.